Premenstrual exacerbation of asthma. Issue 11 (November 1984) - Gibbs, C J; Coutts, I I; Lock, R; Finnegan, O C; White, R J
Abstract : Questionnaires and twice daily peak expiratory flow measurements were used to evaluate the effects of the menstrual cycle in asthmatic women. Forty per cent of women reported premenstrual deterioration in their symptoms and this was confirmed by peak flow recordings. No correlations were found between premenstrual exacerbation of asthma and symptoms of premenstrual tension, consumption of aspirin, use of the contraceptive pill, cycle length, or behaviour of asthma during pregnancy.